HUBUNGAN PERILAKU HIDUP SEHAT DENGAN PRESTASI AKADEMIK PADA MAHASISWA DI ASRAMA UNIVERSITAS KLABAT - Metty Wuisang (Klabat Journal of Nursing, 2021)
A healthy behaviour is a person's actions or activities carried out by someone, both directly and indirectly, to maintain and improve the health condition. Academic achievements are results that have been achieved from learning activities at school or college that are cognitive and usually are determined through measurement and assessment. The purpose of this study is to determine the relationship between healthy living behaviour and academic achievement. This research use analytic observational with the cross sectional approach. The sampling technique is purposive sampling with a sample size of 258 respondents. Data analysis uses the Spearmen correlation formula. The conclusion that healthy living behaviour with academic achievement has a significant relationship with p = 0.011<0,05. The recommendation for tertiary institutions to improve facilities and regulations that will support the healthy living behaviour of students in improving academic achievements.